Praktik Jual Beli Buah Manggis Borongan di Desa Cibeber dalam Perspektif Ekonomi Islam - Ramadhan, Fauzi Mubarok (CV. Lafadz Jaya, 2024)
This study analyzes the practice of wholesale mangosteen trade (borongan) conducted by the community of Cibeber Village, Kiarapedes Subdistrict, Purwakarta Regency, and its perspective in Islamic Economics. The wholesale trade method employed in this village involves the transaction of goods whose quantities or qualities are not fully known at the time of sale, which in Islamic economics is recognized as involving uncertainty (gharar). This research uses a qualitative approach with case study and field research methods. Data were collected through observations, interviews, and literature reviews. The findings indicate that although the wholesale trade practice is still prevalent due to its convenience for farmers, it contains risks that conflict with Islamic economic principles, particularly related to the uncertainty concerning the goods and price determination. This study also identifies the reasons behind the community's preference for wholesale trading methods in mangosteen transactions and offers suggestions for improving the practice to align with Islamic principles.